Financial Consumer Protection and New Forms of Data Processing Beyond Credit Reporting - World Bank Group (World Bank, Washington, DC, 2018)
New sources of data, as well as new ways of processing such data, have contributed to an ongoing expansion in the availability of digital financial services (DFS) to served, underserved, and unserved consumers. Such data is being used to design and market customer-centric digital financial services, create credit scores for consumers with limited credit histories, meet and facilitate know-your-customer requirements, and minimize the risk of fraud. Yet a great variety of personal information may be used and processed in this context. This discussion note provides an overview of consumer-related benefits and risks arising from the usage of new types of data, beyond traditional credit-reporting frameworks. The note also identifies areas for further research.